Pengaruh Self-Esteem, Efikasi Diri dan Adversity Quotient terhadap Resiliensi Kerja - Maria Cicilia Deva Authary Dei; Zulvia Khalid (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2026)
In the midst of increasingly intense competition in the digital era, organizations are required to possess human resources capable of adapting and enduring various work-related challenges. Therefore, work resilience is considered an important competency that employees must have. This study aims to examine the influence of self- esteem, self-efficacy, and adversity quotient on work resilience among supervisor members of Independent Herbalife Nutrition Indonesia in South Jakarta. This research employs a descriptive quantitative approach. Data were collected through the distribution of Likert-scale questionnaires to 103 respondents using a saturated sampling technique. The data obtained were analyzed using multiple linear regression analysis with the assistance of Microsoft Excel 2019 and IBM SPSS version 22. The results of the study indicate that self-efficacy has a positive and significant effect on work resilience. Meanwhile, self-esteem and adversity quotient do not have a significant partial effect on work resilience. However, simultaneously, self-esteem, self-efficacy, and adversity quotient have a significant effect on work resilience.